Multidisciplinary study of the hanging wall of the Kiirunavaara iron ore deposit, northern Sweden - Jensen, M.; Kashubin, A.; Juhlin, Christopher; Elming, S. (2012)
Potential weakness zones due to mining-related fracture development under the town of Kiruna, Sweden, have been investigated by integration of seismic, gravity, and petrophysical data. Reflection seismic data were acquired along two subparallel 2D profiles within the residential area of the town. The profiles of ~3.5 km, each oriented approximately east-west, nearly perpendicular to the general strike of the local geology, crossed several contact zones between quartz-bearing porphyries, a sequence of interchanging sedimentary rocks (siltstone, sandstone, conglomerate, and agglomerate), and metabasalt. The resulting reflection seismic sections revealed a strong east-dipping reflectivity that is imaged down to approximately 1.5 km. The location and orientation of major features agree well between the profiles and with the surface geology and known contact zones between the different rock types. Our imaging results, supported by traveltime modelling, indicate that the contact zones dip 40°-50° to the east. The deepest and the weakest reflections are associated with a ~60° dipping structure that is presumably related to the Kiirunavaara iron mineralization. Tomographic inversion of refracted arrivals revealed a more detailed image of the velocity distribution in the upper 100-200 m along the profiles, enabling us to identify near-surface low velocity zones. These could be possible weakness zones developed along the lithological contacts and within the geologic units.The structural image obtained from the seismic data was used to constrain data inversion along a 28 km long east-northeast to west-southwest-oriented gravity profile. The resulting density model indicates that the quartz-bearing porphyry in the hanging wall of the Kiirunavaara mineralization can be separated into two blocks oriented parallel to the ore body. One block has an unexpected low density, which could be an indication of extensive fracturing and deformation.